MelastomaTRAITs 1.0: A database of functional traits in M elastomataceae, a large pantropical angiosperm family - Marcelo Reginato; Carlos A. Ordónez‐Parra; João Vitor S. Messeder; Vinicius L. G. Brito; Agnes Dellinger; Ricardo Kriebel; Camilla Marra; Lilian Melo; Tatiana Cornelissen; Lisieux Fuzessy; Patricia Sperotto; Manuela Calderón‐Hernández; et al. (Ecology, 2024)
The recent availability of open‐access repositories of functional traits has revolutionized trait‐based approaches in ecology and evolution. Nevertheless, the underrepresentation of tropical regions and lineages remains a pervasive bias in plant functional trait databases, which constrains large‐scale assessments of plant ecology, evolution, and biogeography. Here, we present MelastomaTRAITs 1.0, a comprehensive and updatable database of functional traits for the pantropical Melastomataceae, the ninth‐largest angiosperm family with 177 genera and more than 5800 species. Melastomataceae encompass species with a wide diversity of growth forms (herbs, shrubs, trees, epiphytes, and woody climbers), habitats (including tropical forests, savannas, grasslands, and wetlands from sea level to montane areas above the treeline), ecological strategies (from pioneer, edge‐adapted and invasive species to shade‐tolerant understory species), geographic distribution (from microendemic to continental‐wide distribution), reproductive, pollination, and seed dispersal systems. MelastomaTRAITs builds on 581 references, such as taxonomic monographs, ecological research, and unpublished data, and includes four whole‐plant traits, six leaf traits, 11 flower traits, 18 fruit traits, and 27 seed traits for 2520 species distributed in 144 genera across all 21 tribes. Most data come from the Neotropics where the family is most species‐rich. Miconieae (the largest tribe) contains the highest number of trait records (49.6%) and species (41.1%) records. The trait types with the most information in the database were whole‐plant traits, flowers, and leaf traits. With the breadth of functional traits recorded, our database helps to fill a gap in information for tropical plants and will significantly improve our capacity for large‐scale trait‐based syntheses across levels of organization, plant–animal interactions, regeneration ecology, and thereby support conservation and restoration programs. There are no copyright restrictions on the dataset; please cite this data paper when reusing the data.

Population structure in Neotropical plants: Integrating pollination biology, topography and climatic niches - Agnes S. Dellinger; Ovidiu Paun; Juliane Baar; Eva M. Temsch; Diana Fernández‐Fernández; Jürg Schönenberger (Molecular Ecology, 2022)
Animal pollinators mediate gene flow among plant populations, but in contrast to well‐studied topographic and (Pleistocene) environmental isolating barriers, their impact on population genetic differentiation remains largely unexplored. Comparing how these multifarious factors drive microevolutionary histories is, however, crucial for better resolving macroevolutionary patterns of plant diversification. Here we combined genomic analyses with landscape genetics and niche modelling across six related Neotropical plant species (424 individuals across 33 localities) differing in pollination strategy to test the hypothesis that highly mobile (vertebrate) pollinators more effectively link isolated localities than less mobile (bee) pollinators. We found consistently higher genetic differentiation ( F ST ) among localities of bee‐ than vertebrate‐pollinated species with increasing geographical distance, topographic barriers and historical climatic instability. High admixture among montane populations further suggested relative climatic stability of Neotropical montane forests during the Pleistocene. Overall, our results indicate that pollinators may differentially impact the potential for allopatric speciation, thereby critically influencing diversification histories at macroevolutionary scales.

Reconstructing geographical parthenogenesis: effects of niche differentiation and reproductive mode on Holocene range expansion of an alpine plant - Bernhard Kirchheimer; Johannes Wessely; Andreas Gattringer; Karl Hülber; Dietmar Moser; Christoph C. F. Schinkel; Marc Appelhans; Simone Klatt; Marco Caccianiga; Agnes Dellinger; Antoine Guisan; Michael Kuttner; et al. (Ecology Letters, 2018)
Asexual taxa often have larger ranges than their sexual progenitors, particularly in areas affected by Pleistocene glaciations. The reasons given for this ‘geographical parthenogenesis’ are contentious, with expansion of the ecological niche or colonisation advantages of uniparental reproduction assumed most important in case of plants. Here, we parameterized a spread model for the alpine buttercup Ranunculus kuepferi and reconstructed the joint Holocene range expansion of its sexual and apomictic cytotype across the European Alps under different simulation settings. We found that, rather than niche broadening or a higher migration rate, a shift of the apomict's niche towards colder conditions per se was crucial as it facilitated overcoming of topographical barriers, a factor likely relevant for many alpine apomicts. More generally, our simulations suggest potentially strong interacting effects of niche differentiation and reproductive modes on range formation of related sexual and asexual taxa arising from their differential sensitivity to minority cytotype disadvantage.

A matter of scale: apparent niche differentiation of diploid and tetraploid plants may depend on extent and grain of analysis - Bernhard Kirchheimer; Christoph C. F. Schinkel; Agnes S. Dellinger; Simone Klatt; Dietmar Moser; Manuela Winkler; Jonathan Lenoir; Marco Caccianiga; Antoine Guisan; Diego Nieto‐Lugilde; Jens‐Christian Svenning; Wilfried Thuiller; et al. (Journal of Biogeography, 2016)
Aim Emerging polyploids may depend on environmental niche shifts for successful establishment. Using the alpine plant Ranunculus kuepferi as a model system, we explore the niche shift hypothesis at different spatial resolutions and in contrasting parts of the species range. Location European Alps. Methods We sampled 12 individuals from each of 102 populations of R. kuepferi across the Alps, determined their ploidy levels, derived coarse‐grain (100 × 100 m) environmental descriptors for all sampling sites by downscaling WorldClim maps, and calculated fine‐scale environmental descriptors (2 × 2 m) from indicator values of the vegetation accompanying the sampled individuals. Both coarse and fine‐scale variables were further computed for 8239 vegetation plots from across the Alps. Subsequently, we compared niche optima and breadths of diploid and tetraploid cytotypes by combining principal components analysis and kernel smoothing procedures. Comparisons were done separately for coarse and fine‐grain data sets and for sympatric, allopatric and the total set of populations. Results All comparisons indicate that the niches of the two cytotypes differ in optima and/or breadths, but results vary in important details. The whole‐range analysis suggests differentiation along the temperature gradient to be most important. However, sympatric comparisons indicate that this climatic shift was not a direct response to competition with diploid ancestors. Moreover, fine‐grained analyses demonstrate niche contraction of tetraploids, especially in the sympatric range, that goes undetected with coarse‐grained data. Main conclusions Although the niche optima of the two cytotypes differ, separation along ecological gradients was probably less decisive for polyploid establishment than a shift towards facultative apomixis, a particularly effective strategy to avoid minority cytotype exclusion. In addition, our results suggest that coarse‐grained analyses overestimate niche breadths of widely distributed taxa. Niche comparison analyses should hence be conducted at environmental data resolutions appropriate for the organism and question under study.